Potensi Endapan Pasir Besi di Daerah Grabag dan Sekitarnya Berdasarkan Data Geomagnet - G.M. Lucki Junursyah; Wanda Rahmat (Jurnal Geologi dan Sumberdaya Mineral, 2019)
The potential of iron sand in Grabag area and its surrounding, Central Java Province, is not fully known yet because it is covered by thick alluvium, so that mining activities are done unmanaged without seeing the effect of environmental damage caused. This study uses reduction to the pole and upward continuation processing and analysis for Geomagnetic data in order to spread of lateral magnetic anomalies (map) and forward modelling for vertical magnetic anomalies (2D cross-sections). Based on the dispersion of magnetic anomaly, it is known that iron sand potential in the research area is located on old alluvium deposits with depth around 60 m and young coast alluvium sedimentation with depth around of 20 m, forming a lens as sand dump or river bank, followed by lane of ancient river flow pattern with thickness reaching Â±10 m. The potential area is estimated to reach 26,329,188 mÂ² with the calculation of hypothetical reserves reaching 69,575 Ton on the southwest and 5,880, 213 Ton in the northwest of the research area. The results of this study are expected to be used as reference for further research, so that it can menage iron sand mining activities more regularly and not caused environmental damaged.Keywords: Geomagnetic, Iron Sand, Alluvium.Â